Discovering the wonders of Malaysian orchids: unveiling Vanilla Norashikiniana - Go, Rusea; Raffi, Akmal (Universiti Putra Malaysia Press, 2019)
Orchids as one of the largest flowering plant family numbering more than 25,000 species worldwide are part of the priceless green and aesthetic bioresources in our country. Malaysia is home to over 3,000 species of the most beautiful and mysterious plants species, with more than 1,000 are found in Peninsular Malaysia. Many wild species are high priced commodity as Gold of Kinabalu, Paphiopedilum rothchildianum ranked the 5th most expensive orchid in the world with price tagged at £3,800 ten years ago needed at least 15 years to flower and is currently claimed to be on the verge of extinction, which could push prices up even more. The vanilla orchid, which is represented by 12 species in Malaysia are another huge economic potential commodity species with at least three species that could produce vanilla essence.